Pengaruh Work Environment, Kontrak Psikologis, Dan Work Life Balance Terhadap Turnover Intention Pada Karyawan (Studi Kasus Pada PT ZEE Indonesia) - Fitri Dwi Nur Khasanah; Muhammad Ridwan Basalamah; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to examine the effect of work environment, psychological contract, and work life balance on employee turnover intention "(Case Study at PT. ZEE INDONESIA)". This research was conducted using quantitative descriptive analysis method. The sample in this study used a saturated sample, ie the entire population was the sample with 45 employees as respondents. The data analysis technique used is multiple linear regression.Based on the results of data analysis, it can be concluded simultaneously or jointly that the work environment, psychological contract, and work life balance have a significant effect on turnover intention. While partially the work environment has no significant effect on turnover intention, psychological contracts have a significant effect on turnover intention, and work life balance have a significant effect on turnover intention. Keywords :  Work  Environment,  Psychological  Contract, Employment  Contract,  Work  Life  Balance,  Turnover Intention.